Método dos elementos finitos através da análise isogeométrica: uma introdução - Gomes Filho, Hélio (2016)
The Isogeometric Analysis is a method that combine the Finite Elements Method with NonUniform Rational Basis Spline (NURBS). The NURBS is used to describe the geometry with great flexibility, and it can also work as basis functions. The main concepts of NURBS are presented in this study, and how to apply the method to solve ordinary and partial differential equations. A comparison between the isogeometric analysis and the classical finite elements method is showed to contrast the error behavior in both methods, and the advantages of describe exactly a domain. The elasticity problem in two-dimensional and three-dimensional model are performed as application of the isogeometric analysis, and as exemple it was developed a model of a shell based on a real structure.